Second Language Learning Motivation: A Case Study of Students with Visual Impairment at a University in Hanoi - Ngô, Phương Thanh (2020)
The study employs case study to investigate what motivate visually impaired students to learn L2. The research goals are achieved by means of qualitative data. The study was carried out by some steps as follows: First, the language learning autobiography was employed to find out their second language learning stories in the connection with learning motivation. Second, personal interviews with two students were conducted in order to: • Study their rationales for learning • Study their past and present learning experience to find out how L2 learning motivation was generated and changed • Find out the difficulties in students’ L2 language learning and their impacts on L2 motivation. Then, the data were collected, sorted and analyzed qualitatively to obtain realistic results. To end with, pedagogical implications for enhancing students’ motivation in L2 language learning was proposed based on the results found from all data collection instruments.